Hubungan Dukungan Keluarga dan Spiritual terhadap Kualitas Hidup Penderita Diabetes Melitus yang Menjalani Hemodialisa di RSUD Arifin Achmad Provinsi Riau - Irwan, Muhammad; Ginting, Chrismis Novalinda; Chiuman, Linda (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT Diabetes mellitus (DM) is a metabolic disease that can significantly reduce patients' quality of life due to long-term complications. This study aims to analyze the relationship between family support, spirituality, and health perception on the quality of life of diabetes mellitus patients undergoing hemodialysis at RSUD Arifin Achmad, Riau Province. This research employed a quantitative approach with a cross-sectional design. Data were collected using validated questionnaires, including the Perceived Social Support-Family (PSS-Fa), Daily Spiritual Experience Scale (DSES), and WHOQOL-BREF. A total of 100 respondents were selected using the Slovin formula and analyzed using Partial Least Square (PLS). The findings revealed that family support had a significant and dominant influence on the quality of life of patients (path coefficient 0.320; p < 0.05), particularly in providing emotional, instrumental, and informational support. Spirituality also significantly contributed (path coefficient 0.187; p < 0.05) by enhancing psychological resilience and providing a sense of purpose. The combination of these two variables explained 33% of the variance in patients' quality of life, while the remaining percentage was influenced by other factors outside the scope of this study. These findings indicate that a holistic approach involving family support and spirituality can comprehensively enhance patients' physical, emotional, and social well-being. In conclusion, family support and spirituality play crucial roles in improving the quality of life of DM patients undergoing hemodialysis. Interventions integrating family education, spiritual counseling, and multidimensional approaches in hospital care programs are necessary to optimize patients' quality of life. Keywords: Diabetes Mellitus, Family Support, Spirituality, Quality of Life,       Hemodialysis  ABSTRAK Diabetes melitus (DM) adalah penyakit metabolik yang dapat menurunkan kualitas hidup pasien akibat komplikasi jangka panjang. Penelitian ini bertujuan untuk menganalisis hubungan antara dukungan keluarga, spiritualitas, dan persepsi kesehatan terhadap kualitas hidup pasien diabetes melitus yang menjalani hemodialisa di RSUD Arifin Achmad, Provinsi Riau. Studi ini menggunakan pendekatan kuantitatif dengan desain cross-sectional. Data dikumpulkan menggunakan kuesioner baku, meliputi Perceived Social Support-Family (PSS-Fa), Daily Spiritual Experience Scale (DSES), dan WHOQOL-BREF. Sampel sebanyak 100 responden dipilih menggunakan metode Slovin dan dianalisis menggunakan Partial Least Square (PLS). Hasil penelitian menunjukkan bahwa dukungan keluarga memiliki pengaruh signifikan dan dominan terhadap kualitas hidup pasien (koefisien jalur 0.320; p < 0.05), terutama dalam memberikan dukungan emosional, instrumental, dan informasional. Spiritualitas juga memberikan kontribusi signifikan (koefisien jalur 0.187; p < 0.05) melalui penguatan psikologis dan pemberian makna hidup. Kombinasi kedua variabel menjelaskan 33% variansi kualitas hidup pasien, sementara sisanya dipengaruhi oleh faktor lain di luar penelitian ini. Temuan ini menunjukkan bahwa pendekatan holistik yang melibatkan dukungan keluarga dan spiritualitas dapat meningkatkan kesejahteraan fisik, emosional, dan sosial pasien secara menyeluruh. Dari hasil penelitian dapat disimpulkan dukungan keluarga dan spiritualitas memiliki peran penting dalam meningkatkan kualitas hidup pasien DM yang menjalani hemodialisa. Diperlukan intervensi yang mengintegrasikan edukasi keluarga, konseling spiritual, dan pendekatan multidimensi dalam program perawatan rumah sakit untuk mengoptimalkan kualitas hidup pasien. Kata Kunci: Diabetes Melitus, Dukungan Keluarga, Spiritualitas, Kualitas Hidup,                   Hemodialisa